The Role of Investment in The Economic Growth Rate of Karanganyar Regency - Pancaningsih, Rahayu; Habiibika Baaq, Shalli; Fadila, Sarah (LPPM Universitas Duta Bangsa Surakarta, 2023)
Economic growth is seen as a long-term economic problem in a country. The ability to produce goods and services of a country will also continue to increase in subsequent periods. The success of economic development in a region occurs because economic growth continues to increase, so that people's income and community welfare are also expected to continue to increase. Investment is one of the factors that influence economic growth, especially in Karanganyar Regency, seen from the data on the Realization of Domestic Investment (PMDN) and Foreign Investment (PMA). The purpose of this study is to analyze how the role of investment on economic growth in Karanganyar Regency and so that this research can be used as a reference for Karanganyar Regency in its regional economic development. The method used in this research uses the non-participant observation method. And the secondary data for this study were obtained from the Central Statistics Agency (BPS) of Karanganyar Regency from 2016 to 2021. Then the data was analyzed using multiple linear regression analysis using the statistical package social sciense (SPSS) version 25 application.